Preparation method of reinforced copper-based electrical contact composite material based on carbon nanotubes
By introducing carbon nanotubes into CuCr electrical contacts and adopting powder metallurgy and hot extrusion processes, the ablation and wear of CuCr electrical contacts under the action of high arc temperature is solved, and its anti-arc corrosion performance and service life are significantly improved.
Patent Information
- Application Number
- CN202411868940.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-28
AI Technical Summary
Existing CuCr electrical contacts are easily welded or ablated and worn under the action of high arc temperature, resulting in electrical failure. The low conductivity and high density difference of Cr lead to arc aggregation, shortening the life of electrical contacts.
By adding carbon nanotubes (CNTs) to CuCr composites, the conductive and thermal conductivity of CNTs are used to improve mass transfer in arc erosion, and carbon nanotube reinforced copper-chromium composites are prepared in combination with powder metallurgy and hot extrusion processes to improve arc erosion resistance and mechanical properties.
It significantly improves the arc erosion resistance and service life of CuCr electrical contacts, maintains good electrical conductivity and thermal conductivity, and avoids arc aggregation and extends the service life of electrical contacts.
Smart Images

Figure CN119710341A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a carbon nanotube-reinforced copper-based electric contact composite material, belonging to the technical field of electric contact preparation. Background Art
[0002] Electric contacts are responsible for connecting, disconnecting and transmitting electric current in electrical and electronic devices. They are the main actuators for electrical switching operations. In view of their important position in electrical appliances, they are also called the "heart of electrical appliances". While electric contacts are subjected to the impact and friction of the electrical mechanism, they are also eroded by the arc during the electrical switching process. If the electric contacts are welded or excessively worn by the arc under the high temperature of the arc, the entire appliance will fail. Therefore, as a key material that affects the switching ability and reliability of electrical appliances, the material of the electric contact needs to further improve its arc erosion resistance.
[0003] At present, electrical contact materials mainly use silver-based and copper-based composite materials according to the application scenarios. In copper-chromium electrical contacts, copper has a low melting point, high electrical conductivity and high thermal conductivity, which is beneficial to improve the breaking capacity of vacuum circuit breakers in electrical contact materials, while chromium has a high melting point, a low cutoff value and a strong affinity for oxygen, which can make the vacuum circuit breaker have high voltage resistance, ablation resistance, and welding resistance. However, during the electrical contact operation of the CuCr electrical contact, since the work function of Cr is lower than that of Cu, the arc will be generated preferentially on the Cr phase, and the molten pool formed by the arc burning will cause the Cr phase to agglomerate due to the density difference between Cu and Cr. In addition, since Cr itself has poor thermal conductivity and low electrical conductivity, it will further cause the arc to gather and will secondary increase the Cr energy accumulation on the surface of the electrical contact, which will eventually reduce the arc erosion area on the surface of the electrical contact and increase the depth, accelerating the failure of the electrical contact. In addition, the CuCr electrical contacts currently used all have high Cr content. The poor conductivity of Cr itself will also cause the electrical conductivity of the electrical contacts to decrease, which also affects the arc erosion resistance of the CuCr electrical contacts. Therefore, how to improve the arc erosion resistance of the CuCr electrical contacts and improve the local concentration of arcs is the key issue to extend the life of electrical contact materials. Summary of the invention
[0004] In view of this, the present invention provides a preparation method of a carbon nanotube-reinforced copper-based electrical contact composite material. On the one hand, CNTs are added to the CuCr composite material, relying on the excellent axial electrical and thermal conductivity of the carbon nanotubes to improve the mass transfer in arc erosion and increase the service life of the electrical contact; on the other hand, the carbon nanotube-reinforced copper-chromium composite material is prepared by combining powder metallurgy and hot extrusion processes. The prepared composite material exhibits excellent anti-arc erosion performance while having good mechanical properties and electrical conductivity, meeting the demand for a long service life of the electrical contact.
[0005] The objectives of the present invention are achieved through the following technical solutions.
[0006] A method for preparing a carbon nanotube-reinforced copper-based electrical contact composite material comprises the following steps:
[0007] (1) uniformly mixing reinforcement powder, copper (Cu) powder and chromium (Cr) powder to obtain a mixed powder;
[0008] (2) placing the mixed powder into a mold and performing hot pressing and sintering to consolidate the powder to form a carbon nanotube reinforced copper-chromium composite material block, referred to as a CNTs / Cu-Cr composite material block;
[0009] (3) The CNTs / Cu-Cr composite material block is subjected to an extrusion deformation treatment at 800-900° C., thereby completing the preparation of the carbon nanotube-reinforced copper-based electrical contact composite material;
[0010] The reinforcing body powder is unmodified carbon nanotube (CNTs) powder, or surface-modified carbon nanotube powder with copper nanoparticles attached to the surface.
[0011] Furthermore, in step (1), the ratio of the mass of the reinforcement powder to the sum of the mass of the copper powder and the chromium powder is 1:100 to 2.1:100, and the mass percentage of the chromium powder in the copper powder and the chromium powder is 10 to 20%.
[0012] Furthermore, the mixed powder described in step (1) is obtained by ball milling, which specifically includes the following steps: adding reinforcement powder, copper powder and chromium powder into a ball mill, adding an organic solvent as a wet grinding medium, setting the ball-to-material ratio to 10:1-15:1 and the ball milling speed to 300-400 r / min, ball milling for 240-360 min under an inert gas protective atmosphere, and vacuum drying after ball milling to remove the organic solvent to obtain a uniformly mixed mixed powder.
[0013] Furthermore, the surface-modified carbon nanotube powder with copper nanoparticles attached to the surface can be prepared by the following method:
[0014] Copper acetate powder (Cu(CH3COO)2·H2O), carbon nanotube powder and water are prepared into a uniform mixed solution;
[0015] The mixed solution is spray pyrolyzed to form CNTs / CuO composite powder;
[0016] The CNTs / CuO composite powder is heated and reduced to form a CNTs / Cu composite powder. The CNTs / Cu composite powder is a surface-modified carbon nanotube powder with copper nanoparticles attached to the surface.
[0017] Furthermore, in the mixed solution, the concentration of cupric acetate is 0.016-0.024 g / mL, and the concentration of carbon nanotubes is 0.08-0.12 wt.%.
[0018] Furthermore, the mixed solution is subjected to heat treatment at 650-750° C. to form CNTs / CuO composite powders by forming small droplets formed by ultrasonic atomization.
[0019] Furthermore, the CNTs / CuO composite powder is heated and reduced at 300-400°C using H2 as a reducing gas.
[0020] Furthermore, the carbon nanotubes are single-walled, double-walled or multi-walled carbon nanotubes with an outer diameter of 50 to 100 nm.
[0021] Furthermore, the particle size of the Cu powder is 20-50 μm, and the particle size of the Cr powder is 200-500 nm. In addition, the morphology of the Cu powder and the Cr powder can be any regular shape or any irregular shape.
[0022] Furthermore, in step (2), the sintering temperature is 700-900° C., the sintering pressure is 30-50 MPa, and the sintering time is 5-15 min.
[0023] Furthermore, in step (3), the extrusion ratio is 15 to 25. More preferably, the extrusion speed is 4 to 10 mm / s.
[0024] Beneficial effects:
[0025] (1) The present invention introduces CNTs into the traditional CuCr electrical contact material, and can utilize the excellent axial electrical and thermal conductivity of CNTs to improve mass transfer during arc erosion, thereby increasing the service life of the CuCr electrical contact. In addition, compared with unmodified CNTs, the use of copper nanoparticles to modify the surface of CNTs can effectively improve the density difference between the CNTs reinforcement and the CuCr matrix, improve the dispersibility of CNTs in the CuCr matrix, and prevent agglomeration to better exert the axial electrical and thermal properties of CNTs; the modified carbon nanotubes can better form an arc path in the CuCr matrix, further disperse the arc, effectively alleviate the ablation and damage of the electrical contact surface under the action of the arc, and also provide a basis for the subsequent Cr x C y provides conditions for the formation of; in the molten pool formed during the electrical contact on-off process, the addition of modified CNTs can increase the viscosity of the molten pool, thereby reducing the mass loss caused by spatter.
[0026] (2) The present invention adopts powder metallurgy technology and hot extrusion technology to prepare a composite material based on carbon nanotubes reinforced copper-based electrical contacts. During the sintering and hot extrusion process of powder metallurgy, CNTs and Cr undergo high-temperature thermal diffusion, which can not only refine the Cr grain size, but also hinder the segregation of Cr in the Cu matrix, effectively disperse the arc, increase the molten pool area, and reduce the arc erosion depth, thereby effectively improving the arc erosion resistance of the CuCr electrical contact. In addition, the interface reaction can also occur in situ during the hot extrusion process to generate Cr x C y The transition layer improves the interface bonding between the CuCr matrix and the CNTs reinforcement, so that the CNTs / Cu-Cr composite material can maintain good electrical conductivity and thermal conductivity while obtaining excellent arc erosion resistance; and after hot extrusion, the Cr and Cu grains are elongated, achieving axial directional arrangement of Cr, reducing radial electron scattering, and facilitating the smooth movement of the arc, thereby facilitating the improvement of the service life of the electrical contact.
[0027] (3) The spray pyrolysis method can not only achieve the attachment of nano-Cu particles on the surface of CNTs, but also regulate the particle size and distribution of Cu particles on CNTs by changing the concentration of the precursor solution, thereby better improving the wettability between CNTs and the Cu matrix, making the two have a better combination.
[0028] (4) The mixed powder is obtained by ball milling, which can effectively avoid the aggregation of Cr in Cu and achieve uniform dispersion of CNTs in CuCr. Moreover, CuCr forms flakes under the action of ball milling, which has a larger specific surface area and provides more attachment sites for the attachment of CNTs, thus realizing the embedding of CNTs in the CuCr matrix, which is beneficial to the dispersion of CNTs in CuCr and improves the performance of the composite material.
[0029] (5) The preparation method of the present invention is simple to operate, has a stable preparation process, a short preparation cycle, and is highly practical. It provides technical guidance for the research on the preparation of electrical contact materials with high arc erosion resistance and long service life, and has good application prospects in the field of power electronic materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The following are scanning electron microscope (SEM) images and electron probe X-ray microanalysis (EPMA) surface scan images of the Cu-Cr composite powder in step (2) of Example 1 at different magnifications.
[0031] Figure 2 The scanning electron microscope (SEM) images of the CNTs / Cu-Cr composite powder in step (2) of Example 1 at different magnifications.
[0032] Figure 3It is a comparison diagram of stress-strain curves of the CNTs / Cu-Cr composite material prepared in Example 1 and the Cu-Cr composite material prepared in Comparative Example 1.
[0033] Figure 4 This is a comparison chart of the conductivity and hardness change bar graphs of the CNTs / Cu-Cr composite material prepared in Example 1 and the Cu-Cr composite material prepared in Comparative Example 1.
[0034] Figure 5 The transmission electron microscope (TEM) image of the CNTs / Cu-Cr composite material prepared in Example 1 and the corresponding position line scanning image.
[0035] Figure 6 This is a comparison chart of Cr grain sizes of the CNTs / Cu-Cr composite material prepared in Example 1 and the Cu-Cr composite material prepared in Comparative Example 1.
[0036] Figure 7 This is a comparison chart of arc energy and arc duration of the CNTs / Cu-Cr composite material prepared in Example 1 and the Cu-Cr composite material prepared in Comparative Example 1.
[0037] Figure 8 It is a comparison diagram of stress-strain curves of the CNTs / Cu-Cr composite material prepared in Example 2 and the Cu-Cr composite material prepared in Comparative Example 2.
[0038] Fig. 9 This is a comparative bar graph of the conductivity and hardness changes of the CNTs / Cu-Cr composite material prepared in Example 2 and the Cu-Cr composite material prepared in Comparative Example 2.
[0039] Fig.10 This is a comparison chart of arc energy and arc duration of the CNTs / Cu-Cr composite material prepared in Example 2 and the Cu-Cr composite material prepared in Comparative Example 2.
[0040] Fig.11 It is a comparison diagram of stress-strain curves of the CNTs / Cu-Cr composite material prepared in Example 3 and the Cu-Cr composite material prepared in Comparative Example 3.
[0041] Fig.12 This is a comparative bar chart of the conductivity and hardness changes of the CNTs / Cu-Cr composite material prepared in Example 3 and the Cu-Cr composite material prepared in Comparative Example 3.
[0042] Fig.13 This is a comparison chart of arc energy and arc duration of the CNTs / Cu-Cr composite material prepared in Example 3 and the Cu-Cr composite material prepared in Comparative Example 3. DETAILED DESCRIPTION
[0043] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments, wherein the methods are conventional methods unless otherwise specified, and the raw materials can be obtained from public commercial channels unless otherwise specified.
[0044] In the following embodiments:
[0045] The CNTs dispersion has a purity of 98wt.%, multi-walled, and an outer diameter of 50-100nm, obtained from Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences;
[0046] Cu(CH3COO)2·H2O was analytically pure (AR≥99%) and was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0047] The purity of Cu powder is 99.9%, the particle size is 20-50μm, and the morphology is dendritic. Shanghai Naio Nano Technology Co., Ltd.
[0048] Cr powder has a purity of 99.5%, a spherical shape, and a particle size of 300-500 nm. It is from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0049] Scanning electron microscope: NovaNano-450, FEI, USA;
[0050] Mechanical properties characterization: Tensile tests were carried out at room temperature using a universal tensile testing machine (AUTOGRAPHAG-I, Shimadzu Corporation, Japan), where the sample size (dog bone type) was 16 mm × 2 mm × 1.5 mm (length × width × thickness), and the tensile rate was 0.2 mm / min.
[0051] Electrical contact performance characterization: The electrical contact test was conducted at room temperature using an electrical contact material tester (JF04C, Kunming, China). The test voltage was 24 V, the current was 10 A, the breaking times were 5000, the opening distance was 1 mm, and the breaking time was 1 s.
[0052] Example 1
[0053] A method for preparing a carbon nanotube-reinforced copper-based electrical contact composite material comprises the following steps:
[0054] (1) adding the CNTs dispersion into the Cu(CH3COO)2·H2O solution and dispersing by ultrasonic for 10 min to obtain a mixed solution, wherein the concentration of CNTs in the mixed solution is 0.08 wt.% and the concentration of Cu(CH3COO)2·H2O is 0.016 g / mL;
[0055] The mixed solution was ultrasonically atomized into small droplets and heat-treated in a tube furnace at 650°C to obtain CNTs / CuO composite powders by spray pyrolysis.
[0056] The CNTs / CuO composite powder was placed in a vacuum tube furnace, and reduced at 300°C for 120 minutes using Ar / H2 as a protective reducing gas to obtain a CNTs / Cu composite powder, that is, a surface-modified carbon nanotube powder with copper nanoparticles attached to the surface;
[0057] (2) 36 g of Cu powder and 4 g of Cr powder were added to a ball mill, the ball-to-material ratio was set to 10:1, the ball mill speed was set to 300 r / min, and the ball milling time was set to 60 min to obtain a Cu-Cr composite powder with the morphology as shown in FIG. Figure 1 As shown;
[0058] 0.4 g CNTs / Cu composite powder and 39.6 g Cu-Cr composite powder were added to a ball mill, and 1 / 4 of the volume of alcohol was added to the ball mill. Argon was used as the protective gas, and the ball-to-material ratio was 10:1. The ball milling was carried out at a speed of 300 r / min for 240 min. After the ball milling was completed, it was dried under vacuum conditions to remove the alcohol to obtain a uniformly mixed mixed powder, which was referred to as CNTs / Cu-Cr composite powder. The morphology is as follows: Figure 2 As shown;
[0059] (3) 40 g of CNTs / Cu-Cr composite powder was loaded into a graphite sintering mold with an inner diameter of 20 mm, and the mold was placed in a fast hot pressing sintering furnace (FHP). The furnace was evacuated to vacuum and sintered at 700 °C and 30 MPa for 5 min. After sintering, the furnace was cooled to obtain a CNTs / Cu-Cr composite block.
[0060] (4) The CNTs / Cu-Cr composite material block is subjected to extrusion deformation treatment by using a hot extruder, wherein the extrusion temperature is 800°C, the extrusion ratio is 15, and the extrusion speed is 4 mm / s. After extrusion, a carbon nanotube-reinforced copper-based electrical contact composite material is obtained, which is abbreviated as CNTs / Cu-Cr composite material.
[0061] In order to verify the dispersion effect of ball milling on chromium and carbon nanotubes, the morphology of the Cu-Cr composite powder and CNTs / Cu-Cr composite powder after ball milling was characterized respectively. Figure 1 (a) and Figure 1 (b) is the SEM image of Cu-Cr composite powder at different magnifications. Figure 1 (b) EPMA surface scanning was performed, and the element distribution is shown in Figure 1 (c) and Figure 1 As shown in (d), it can be observed that the Cr particles are uniformly dispersed in the Cu matrix, and the dendritic copper powder is well ground into flakes by ball milling. Figure 2 (a) and Figure 2As shown in (b), after ball milling, CNTs are evenly dispersed in the Cu-Cr composite powder, which is conducive to the subsequent reaction heat diffusion of Cr and CNTs, increases the viscosity of the molten pool caused by arc erosion during the electrical contact process, improves the viscosity of Cr in the Cu molten pool, avoids arc concentration caused by Cr phase agglomeration, and effectively improves the arc erosion resistance of the contact and the service life of the electric contact.
[0062] Figure 5 (a) is a TEM image of the CNTs / Cu-Cr composite block after extrusion deformation treatment, and a line scan of the nanoparticles therein shows that the formed nanoparticles have both Cr and C element peaks (e.g. Figure 5 (b) shows that reaction heat diffusion occurred during the hot extrusion process to form Cr x C y Ceramic particles.
[0063] Comparative Example 1
[0064] (1) 36 g of Cu powder and 4 g of Cr powder were added to a ball mill, and 1 / 4 of the volume of alcohol was added to the ball mill. Argon was used as the protective gas, and the ball-to-material ratio was 10:1. The ball mill was carried out at a speed of 300 r / min for 240 min. After the ball milling was completed, it was dried under vacuum conditions to remove the alcohol, and a Cu-Cr composite powder was obtained;
[0065] (2) 40 g of Cu-Cr composite powder was loaded into a graphite sintering mold with an inner diameter of 20 mm, and the mold was placed in a rapid hot pressing sintering furnace. The furnace body was evacuated to vacuum, and sintered at 700 ° C and 30 MPa for 5 min. After sintering, the furnace was cooled to obtain a Cu-Cr composite block;
[0066] (3) The Cu-Cr composite material block is subjected to extrusion deformation treatment by using a hot extruder, wherein the extrusion temperature is 800° C., the extrusion ratio is 15, and the extrusion speed is 4 mm / s. After extrusion, a copper-based electrical contact composite material is obtained, which is abbreviated as Cu-Cr composite material.
[0067] If only Cu powder and Cr powder are mixed, due to the low content of Cr powder, welding or excessive arc ablation and wear will occur during the power-off process due to the high temperature of the arc. In addition, due to the high melting point of Cr, after the Cu matrix forms a molten pool, it still remains in a granular state. Due to the density difference between Cr and Cu, it will be segregated in the molten pool, reducing the service life of the electrical contact. Therefore, using nano copper particles to modify the surface of CNTs can effectively eliminate the density difference between Cu and Cr, improve the wettability of the interface between the two, and not only help the dispersion of CNTs in Cu-Cr composite powders, but also reduce the segregation of Cr phases through reaction heat diffusion, improve the arc erosion resistance of Cu-Cr contacts, and increase service life.
[0068] The mechanical properties of the composite materials prepared in Example 1 and Comparative Example 1 were characterized respectively. The test results are as follows: Figure 3 As shown in the figure, the tensile strength of the composite material of Example 1 (about 420 MPa) is higher than that of the composite material of Comparative Example 1 (276 MPa). This is because the added CNTs reacted and diffused with Cr during the hot extrusion process to form Cr x C y It can effectively refine the Cr grain size, produce obvious fine grain strengthening, and improve the strength of the composite material.
[0069] The conductivity and hardness of the composite materials prepared in Example 1 and Comparative Example 1 were tested respectively. The results are as follows: Figure 4 As shown in the figure, compared with Comparative Example 1, the composite material with surface-modified CNTs added in Example 1 has higher conductivity (about 80% IACS) and higher hardness (increased to about 136 HV). This is because after the added CNTs are subjected to hot extrusion deformation treatment, the Cr and CNTs are oriented in the composite material, and most of the Cr phase is elongated into a fibrous shape, which effectively improves the conductivity of the composite material. x C y The formation of ceramic particles is dispersed in the composite material, and Cr x C y Ceramic particles themselves have high hardness, which is beneficial to improving the hardness of the composite material.
[0070] The Cr grain sizes of the composite materials prepared in Example 1 and Comparative Example 1 were statistically analyzed. The results are as follows: Figure 6 As shown, Example 1 ( Figure 6 c and Figure 6 d) Compared with Comparative Example 1 ( Figure 6 a and Figure 6 b), it can be clearly observed that the size of Cr grains has been significantly refined. The addition of CNTs reduces the average grain size of Cr from 4.36μm to 0.28μm, which effectively shows that CNTs react with Cr to generate Cr during hot extrusion. x C y , thereby effectively refining the Cr grain size.
[0071] The composite materials prepared in Example 1 and Comparative Example 1 were tested for electrical contact performance (24V, 10A, 5000 times). The results are as follows: Figure 7As shown in the figure, the arc energy and arc burning time of the composite material of Example 1 are significantly lower than those of the composite material of Comparative Example 1. On the one hand, the surface of CNTs is modified by using copper nanoparticles, which effectively improves the dispersion problem of CNTs; on the other hand, the added CNTs react with Cr during sintering and hot extrusion to form Cr. x C y It effectively increases the viscosity of Cr in the Cu molten pool, hinders the segregation of Cr during the electrical contact process, avoids the arc from concentrating on the Cr phase, thereby dispersing the arc and accelerating heat dissipation. The refined Cr particles can also further disperse the arc, making the arc movement smoother, improving the arc erosion resistance of the electrical contact and extending the service life of the contact.
[0072] Example 2
[0073] A method for preparing a carbon nanotube-reinforced copper-based electrical contact composite material comprises the following steps:
[0074] (1) adding the CNTs dispersion into the Cu(CH3COO)2·H2O solution and dispersing by ultrasonic for 10 min to obtain a mixed solution, wherein the concentration of CNTs in the mixed solution is 0.1 wt.% and the concentration of Cu(CH3COO)2·H2O is 0.02 g / mL;
[0075] The mixed solution was ultrasonically atomized into small droplets and heat-treated in a tube furnace at 700°C to obtain CNTs / CuO composite powders by spray pyrolysis.
[0076] The CNTs / CuO composite powder was placed in a vacuum tube furnace, and reduced at 350°C for 120 minutes using Ar / H2 as a protective reducing gas to obtain a CNTs / Cu composite powder, that is, a surface-modified carbon nanotube powder with copper nanoparticles attached to the surface;
[0077] (2) 34 g of Cu powder and 6 g of Cr powder were added into a ball mill, the ball-to-material ratio was set to 10:1, the ball mill speed was set to 300 r / min, and the ball milling time was set to 60 min to obtain Cu-Cr composite powder;
[0078] 0.6 g of CNTs / Cu composite powder and 39.4 g of Cu-Cr composite powder were added to a ball mill, and 1 / 4 of the volume of alcohol was added to the ball mill. Argon was used as a protective gas, and the ball-to-material ratio was 12.5:1. The ball milling was carried out at a speed of 350 r / min for 300 min. After the ball milling was completed, it was dried under vacuum conditions to remove the alcohol to obtain a uniformly mixed mixed powder, which was abbreviated as CNTs / Cu-Cr composite powder.
[0079] (3) 40 g of CNTs / Cu-Cr composite powder was loaded into a graphite sintering mold with an inner diameter of 20 mm, and the mold was placed in a fast hot pressing sintering furnace (FHP), the furnace body was evacuated to vacuum, and sintered at 800 °C and 40 MPa for 10 min. After sintering, the furnace was cooled to obtain a CNTs / Cu-Cr composite block;
[0080] (4) The CNTs / Cu-Cr composite material block is subjected to extrusion deformation treatment by using a hot extruder, wherein the extrusion temperature is 850°C, the extrusion ratio is 20, and the extrusion speed is 7 mm / s. After extrusion, a carbon nanotube-reinforced copper-based electrical contact composite material is obtained, which is abbreviated as CNTs / Cu-Cr composite material.
[0081] Comparative Example 2
[0082] (1) 36 g of Cu powder and 4 g of Cr powder were added to a ball mill, and 1 / 4 of the volume of alcohol was added to the ball mill. Argon was used as the protective gas, and the ball-to-material ratio was 12.5:1. The ball mill was carried out at a speed of 350 r / min for 300 min. After the ball milling was completed, it was dried under vacuum conditions to remove the alcohol, and a Cu-Cr composite powder was obtained;
[0083] (2) 40 g of Cu-Cr composite powder was loaded into a graphite sintering mold with an inner diameter of 20 mm, and the mold was placed in a rapid hot pressing sintering furnace. The furnace body was evacuated to vacuum, and sintered at 800 ° C and 40 MPa for 10 min. After sintering, the furnace was cooled to obtain a Cu-Cr composite block;
[0084] (3) The Cu-Cr composite material block is subjected to extrusion deformation treatment by using a hot extruder, wherein the extrusion temperature is 850° C., the extrusion ratio is 20, and the extrusion speed is 7 mm / s. After extrusion, a copper-based electrical contact composite material is obtained, which is abbreviated as Cu-Cr composite material.
[0085] The mechanical properties of the composite materials prepared in Example 2 and Comparative Example 2 were characterized respectively. The test results are as follows: Figure 8 As shown, the tensile strength of the composite material of Example 2 (about 443 MPa) is improved compared with the tensile strength of the composite material of Comparative Example 2 (287 MPa).
[0086] The conductivity and hardness of the composite materials prepared in Example 2 and Comparative Example 2 were tested respectively. The results are as follows: Fig. 9 As shown, compared with Comparative Example 2, the composite material of Example 2 with surface-modified CNTs has higher conductivity (about 81% IACS) and higher hardness (increased to about 145 HV).
[0087] The composite materials prepared in Example 2 and Comparative Example 2 were tested for electrical contact performance (24V, 10A, 5000 times). The results are as follows: Fig.10 As shown, the arc energy and arc burning time of the composite material of Example 2 are significantly reduced compared with the arc energy and arc burning time of the composite material of Comparative Example 2, and the arc energy and arc burning time of the composite material of Example 2 are more stable than those of Comparative Example 2 during the breaking process.
[0088] Example 3
[0089] A method for preparing a carbon nanotube-reinforced copper-based electrical contact composite material comprises the following steps:
[0090] (1) adding the CNTs dispersion into the Cu(CH3COO)2·H2O solution and dispersing by ultrasonic for 10 min to obtain a mixed solution, wherein the concentration of CNTs in the mixed solution is 0.12 wt.% and the concentration of Cu(CH3COO)2·H2O is 0.024 g / mL;
[0091] The mixed solution was ultrasonically atomized into small droplets and heat-treated in a tube furnace at 750°C to obtain CNTs / CuO composite powders by spray pyrolysis.
[0092] The CNTs / CuO composite powder is placed in a vacuum tube furnace, and reduced at 400°C for 120 minutes using Ar / H2 as a protective reducing gas to obtain a CNTs / Cu composite powder, that is, a surface-modified carbon nanotube powder with copper nanoparticles attached to the surface;
[0093] (2) 32 g of Cu powder and 8 g of Cr powder were added into a ball mill, the ball-to-material ratio was set to 10:1, the ball mill speed was set to 300 r / min, and the ball milling time was set to 60 min to obtain Cu-Cr composite powder;
[0094] 0.8 g of CNTs / Cu composite powder and 39.2 g of Cu-Cr composite powder were added to a ball mill, and 1 / 4 of the volume of alcohol was added to the ball mill. Argon was used as a protective gas, and the ball-to-material ratio was 15:1. The ball milling was carried out at a speed of 400 r / min for 360 min. After the ball milling was completed, it was dried under vacuum conditions to remove the alcohol to obtain a uniformly mixed mixed powder, which was abbreviated as CNTs / Cu-Cr composite powder.
[0095] (3) 40 g of CNTs / Cu-Cr composite powder was loaded into a graphite sintering mold with an inner diameter of 20 mm, and the mold was placed in a fast hot pressing sintering furnace (FHP), the furnace body was evacuated to vacuum, and sintered at 900 °C and 50 MPa for 15 min. After sintering, the furnace was cooled to obtain a CNTs / Cu-Cr composite block;
[0096] (4) The CNTs / Cu-Cr composite material block is subjected to extrusion deformation treatment by using a hot extruder, wherein the extrusion temperature is 900°C, the extrusion ratio is 25, and the extrusion speed is 10 mm / s. After extrusion, a carbon nanotube-reinforced copper-based electrical contact composite material is obtained, which is abbreviated as CNTs / Cu-Cr composite material.
[0097] Comparative Example 3
[0098] (1) 32 g of Cu powder and 8 g of Cr powder were added to a ball mill, and 1 / 4 of the volume of alcohol was added to the ball mill. Argon was used as the protective gas, and the ball-to-material ratio was 15:1. The ball mill was carried out at a speed of 400 r / min for 360 min. After the ball milling was completed, it was dried under vacuum conditions to remove the alcohol, and a Cu-Cr composite powder was obtained;
[0099] (2) 40 g of Cu-Cr composite powder was loaded into a graphite sintering mold with an inner diameter of 20 mm, and the mold was placed in a rapid hot pressing sintering furnace. The furnace body was evacuated to vacuum, and sintered at 900 ° C and 50 MPa for 15 min. After sintering, the furnace was cooled to obtain a Cu-Cr composite block;
[0100] (3) The Cu-Cr composite material block is subjected to extrusion deformation treatment by using a hot extruder, wherein the extrusion temperature is 900° C., the extrusion ratio is 25, and the extrusion speed is 10 mm / s. After extrusion, a copper-based electrical contact composite material is obtained, which is abbreviated as Cu-Cr composite material.
[0101] The mechanical properties of the composite materials prepared in Example 3 and Comparative Example 3 were characterized respectively. The test results are as follows: Fig.11 As shown, the tensile strength of the composite material of Example 3 (about 413 MPa) is improved compared with the tensile strength of the composite material of Comparative Example 3 (273 MPa).
[0102] The conductivity and hardness of the composite materials prepared in Example 3 and Comparative Example 3 were tested respectively. The results are as follows: Fig.12 As shown, compared with Comparative Example 3, the composite material of Example 3 with the addition of surface-modified CNTs has higher conductivity (about 81% IACS) and higher hardness (increased to about 140 HV).
[0103] The electrical contact performance test (24V, 10A, 5000 times) was carried out on the composite materials prepared in Example 3 and Comparative Example 3. The results are as follows: Fig.13 As shown, the results are Fig.13 As shown, the arc energy and arc burning time of the composite material of Example 3 are significantly reduced compared with the arc energy and arc burning time of the composite material of Comparative Example 3, and the arc energy and arc burning time of the composite material of Example 3 are more stable than those of Comparative Example 3 during the breaking process.
[0104] In summary, the above are only preferred embodiments of the present invention and are not intended to limit the protection scope of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a carbon nanotube-reinforced copper-based electrical contact composite material, characterized in that: The following steps are involved: (1) mixing reinforcement powder, copper powder and chromium powder uniformly to obtain a mixed powder; (2) placing the mixed powder into a mold and performing hot pressing and sintering to consolidate the powder to form a carbon nanotube reinforced copper-chromium composite material block, referred to as a CNTs / Cu-Cr composite material block; (3) The CNTs / Cu-Cr composite material block is subjected to an extrusion deformation treatment at 800-900° C., thereby completing the preparation of the carbon nanotube-reinforced copper-based electrical contact composite material; The reinforcement powder is unmodified carbon nanotube powder or surface-modified carbon nanotube powder with copper nanoparticles attached to the surface.
2. The method for preparing the carbon nanotube-reinforced copper-based electrical contact composite material according to claim 1, characterized in that: In step (1), the ratio of the mass of the reinforcement powder to the sum of the mass of the copper powder and the chromium powder is 1:100 to 2.1:100; and / or, In step (1), the mass percentage of chromium powder in copper powder and chromium powder is 10-20%.
3. The method for preparing the carbon nanotube-reinforced copper-based electrical contact composite material according to claim 1 or 2, characterized in that: The mixed powder of step (1) is obtained by ball milling, which specifically comprises the following steps: Add reinforcement powder, copper powder and chromium powder into a ball mill, add an organic solvent as a wet grinding medium, set the ball-to-material ratio to 10:1-15:1 and the ball mill speed to 300-400 r / min, and ball mill for 240-360 min under an inert gas protective atmosphere. After the ball milling is completed, vacuum drying is performed to remove the organic solvent to obtain a uniformly mixed powder.
4. The method for preparing the carbon nanotube-reinforced copper-based electrical contact composite material according to claim 1, characterized in that: The surface-modified carbon nanotube powder with copper nanoparticles attached to the surface can be prepared by the following method: Copper acetate powder, carbon nanotube powder and water are prepared into a uniform mixed solution; The mixed solution is spray pyrolyzed to form CNTs / CuO composite powder; The CNTs / CuO composite powder is heated and reduced to form a CNTs / Cu composite powder. The CNTs / Cu composite powder is a surface-modified carbon nanotube powder with copper nanoparticles attached to the surface.
5. The method for preparing the carbon nanotube-reinforced copper-based electrical contact composite material according to claim 4, characterized in that: In the mixed solution, the concentration of copper acetate is 0.016-0.024 g / mL, and the concentration of carbon nanotubes is 0.08-0.12 wt.%.
6. The method for preparing the carbon nanotube-reinforced copper-based electrical contact composite material according to claim 4 or 5, characterized in that: The small droplets formed by ultrasonic atomization of the mixed solution are heat-treated at 650-750° C. to form CNTs / CuO composite powder.
7. The method for preparing the carbon nanotube-reinforced copper-based electrical contact composite material according to claim 4 or 5, characterized in that: The CNTs / CuO composite powder was heated and reduced at 300-400°C using H2 as reducing gas.
8. The method for preparing the carbon nanotube-reinforced copper-based electrical contact composite material according to claim 1, characterized in that: The carbon nanotubes are single-walled, double-walled or multi-walled carbon nanotubes with an outer diameter of 50 to 100 nm; and / or, The particle size of the copper powder is 20 to 50 μm, and the particle size of the chromium powder is 200 to 500 nm.
9. The method for preparing the carbon nanotube-reinforced copper-based electrical contact composite material according to claim 1 or 2, characterized in that: In step (2), the sintering temperature is 700-900° C., the sintering pressure is 30-50 MPa, and the sintering time is 5-15 min.
10. The method for preparing the carbon nanotube-reinforced copper-based electrical contact composite material according to claim 1 or 2, characterized in that: In step (3), the extrusion ratio is 15 to 25.
Citation Information
Cited By
Al-tic intermediate alloy with high tic content and preparation method thereof
CN122669256A